2020
DOI: 10.1021/acscatal.0c02794
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Chiral Amines via Biocatalytic Carbene N–H Insertion

Abstract: Optically active amines represent highly valuable building blocks for the synthesis of advanced pharmaceutical intermediates, drug molecules, and biologically active natural products. Hemoproteins have recently emerged as promising biocatalysts for the formation of C-N bonds via carbene transfer, but asymmetric N-H carbene insertion reactions using these or other enzymes have so far been elusive. Here, we report the successful development of a biocatalytic strategy for the asymmetric N-H carbene insertion of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…As a more sustainable and alternative approach to chemical methods, biocatalysis has become an attractive option in preparing chiral N ‐substituted α‐amino acids or their derivatives [1] . Current approaches include N ‐methylation of amino acids and peptides by N ‐methyltransferases, [7] synthesis of N ‐arylated aspartic acids catalyzed by ethylenediamine‐ N , N ′‐disuccinic acid lyase, [8] and reductive amination of α‐ketoacids by NAD(P)H‐dependent oxidoreductases including opine dehydrogenases (OpDHs), ketimine reductases and N ‐methyl amino acid dehydrogenases, [9] and engineered heme‐dependent proteins [10] . However, the current enzymatic toolbox for the synthesis of N ‐substituted α‐amino acids has several limitations including strict stereoselectivity for formation of the l ‐( S )‐enantiomer.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…As a more sustainable and alternative approach to chemical methods, biocatalysis has become an attractive option in preparing chiral N ‐substituted α‐amino acids or their derivatives [1] . Current approaches include N ‐methylation of amino acids and peptides by N ‐methyltransferases, [7] synthesis of N ‐arylated aspartic acids catalyzed by ethylenediamine‐ N , N ′‐disuccinic acid lyase, [8] and reductive amination of α‐ketoacids by NAD(P)H‐dependent oxidoreductases including opine dehydrogenases (OpDHs), ketimine reductases and N ‐methyl amino acid dehydrogenases, [9] and engineered heme‐dependent proteins [10] . However, the current enzymatic toolbox for the synthesis of N ‐substituted α‐amino acids has several limitations including strict stereoselectivity for formation of the l ‐( S )‐enantiomer.…”
Section: Figurementioning
confidence: 99%
“…[1] Current approaches include N-methylation of amino acids and peptides by N-methyltransferases, [7] synthesis of N-arylated aspartic acids catalyzed by ethylenediamine-N,N'-disuccinic acid lyase, [8] and reductive amination of a-ketoacids by NAD(P)H-dependent oxidoreductases including opine dehydrogenases (OpDHs), ketimine reductases and N-methyl amino acid dehydrogenases, [9] and engineered heme-dependent proteins. [10] However, the current enzymatic toolbox for the synthesis of N-substituted aamino acids has several limitations including strict stereoselectivity for formation of the l-(S)-enantiomer. Many enzyme families have narrow substrate specificities, with respect to either the a-ketoacid or amine partner, with high activities limited to simple primary amines such as methylamine.…”
mentioning
confidence: 99%
“…In the last several years, empowered by directed evolution, metallo-haem-dependent enzymes (cytochromes P450, cytochromes c and globins, for example) have exhibited an impressive ability to catalyze non-natural carbene-and nitrene-transfer reactions with high efficiency and selectivity. Specifically, haem proteins have been engineered to perform carbene N-H insertion reactions with catalytic efficiency far exceeding their small-molecule counterparts (up to thousands of total turnover numbers (TTN)) [11][12][13][14] . However, compared to cyclopropanation 15 , C-H insertion 16 and many other carbene transfer reactions also catalyzed by haem proteins 17,18 , N-H insertion reactions are still underdeveloped, especially with respect to high stereocontrol.In small-molecule catalysis, a common strategy for asymmetric N-H insertion is to employ a transition-metal catalyst for carbene transfer along with a separate chiral proton-transfer catalyst (PTC) for stereoinduction (Fig.…”
mentioning
confidence: 99%
“…Several studies have reported that the modication of diazoester substituents causes a signicant impact on the activities and selectivities of carbene transfer reactions. 6,52 The G4-Feporphyrin-catalyzed cyclopropanation has been characterized to proceed through a catalytic IPC intermediate. 34 Diazoester reagents attack the active [Fe] center to form an IPC intermediate and release one molecule of N 2 .…”
Section: Resultsmentioning
confidence: 99%